2001
DOI: 10.1302/0301-620x.83b7.0830963
|View full text |Cite
|
Sign up to set email alerts
|

The coagulative and cardiorespiratory responses to reamed intramedullary nailing of isolated fractures

Abstract: We measured the changes during operation in seven markers of coagulation in a prospective series of 84 patients with fractures of the tibia or femur who were undergoing reamed intramedullary nailing. All patients were also continually monitored using transoesophageal echocardiography to assess marrow embolism. In a subset of 40 patients, intraoperative cardiopulmonary function was monitored, using pulmonary and systemic arterial catheterisation.The procedure produced a significant increase in prothrombin time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 46 publications
0
15
0
1
Order By: Relevance
“…7 Unreamed nailing does not have this effect, but no clinical study has shown a convincing difference in cardiorespiratory complications between the two methods of nailing. 8 Advocates of the unreamed nail suggest that the risk of infection increases with reaming as a result of disturbing the endosteal blood supply, especially in open tibial fractures in which the pre-carious blood supply and lack of soft-tissue cover predispose to nonunion and infection. 9,10 There is a lack of randomised, controlled trials in the literature which compare the rates of infection and nonunion in unreamed and reamed IM nailing.…”
mentioning
confidence: 99%
“…7 Unreamed nailing does not have this effect, but no clinical study has shown a convincing difference in cardiorespiratory complications between the two methods of nailing. 8 Advocates of the unreamed nail suggest that the risk of infection increases with reaming as a result of disturbing the endosteal blood supply, especially in open tibial fractures in which the pre-carious blood supply and lack of soft-tissue cover predispose to nonunion and infection. 9,10 There is a lack of randomised, controlled trials in the literature which compare the rates of infection and nonunion in unreamed and reamed IM nailing.…”
mentioning
confidence: 99%
“…31 Previous large animal studies involving hemorrhagic shock, lung contusion, and reamed intramedullary nailing have demonstrated a similar consumptive coagulopathy with reduction in levels of fibrinogen and AT III. 31 Previous large animal studies involving hemorrhagic shock, lung contusion, and reamed intramedullary nailing have demonstrated a similar consumptive coagulopathy with reduction in levels of fibrinogen and AT III.…”
Section: Discussionmentioning
confidence: 95%
“…31 Previous large animal studies involving hemorrhagic shock, lung contusion, and reamed intramedullary nailing have demonstrated a similar consumptive coagulopathy with reduction in levels of fibrinogen and AT III. 31 The most severe embolic and coagulative responses were measured again after the intramedullary stabilization of pathologic fractures and those with delayed (ie, .48 hours) surgery. 31 The most severe embolic and coagulative responses were measured again after the intramedullary stabilization of pathologic fractures and those with delayed (ie, .48 hours) surgery.…”
Section: Discussionmentioning
confidence: 95%
“…Delays can arise from human error and system inefficiency [5]. Delay in preoperative treatment can be associated with negative outcomes including increased morbidity and mortality [6][7][8]. Unlike preoperative delays, which can include a prolonged waiting time or postponement, perioperative delays occur on the planned day of surgery and include delays getting to the OR and during surgery.…”
Section: Introductionmentioning
confidence: 99%